Analysis Of The Application Of Islamic Business Ethics In The Development Of School Services At Saengsattha School In Thailand - Mutiara Azahra; Syahrul Amsari (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to examine the application of Islamic business ethics principles in the development of educational services at Saengsattha School, Thailand, which is located in a Muslim minority community. Islamic business ethics is positioned as a normative foundation that is not only relevant in commercial activities but also has a strategic role in the governance of educational institutions. This research was conducted using a qualitative approach through field observation techniques, in-depth interviews, document analysis, and literature study. The research informants consisted of school administrators, educators and staff, as well as parents of students as interested parties. The data analysis process was carried out through a series of stages including data reduction, data presentation, and interactive conclusion drawing. The results of the study show that Saengsattha School has implemented Islamic business ethics values, including the principles of monotheism, justice, trustworthiness, responsibility, and benevolence in the development of administrative, academic, and social services. The implementation of these values has had a positive impact on improving the quality of school services, management accountability, and strengthening public trust. However, a number of obstacles were still found, such as the limited understanding of some educators and parents of students regarding the concept of Islamic business ethics, as well as the influence of non-Muslim social and cultural environments. In general, the application of Islamic business ethics is considered effective in supporting the development of school services while maintaining the existence of Islamic values at Saengsattha School. This study is expected to contribute as a conceptual and practical foundation for the development of Islamic ethics-based educational services, especially in areas with a Muslim minority population.